The Difference in Malondialdehyde (MDA) Levels among Normoweight, Overweight, and Obesity in Student of Medicine Program Faculty of Medicine, Mataram University - Ni Putu Visty Widhiani; Ida Ayu Eka Widiastuti; Fitriannisa Faradina Zubaidi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Obesity has emerged as a global issue, including in Indonesia. Previous research has shown that obesity causes oxidative stress, which contributes to degenerative diseases such as type II diabetes mellitus, premature aging, cardiovascular disease, tumors and cancer. Malondialdehyde (MDA) is one of the biomarkers used to assess oxidative stress. The aim of this study was to determine differences in MDA levels in medical students at the University of Mataram based on weight criteria: normal, overweight, and obese. The study included 41 students from the 2021 class of the Medical Education program at the University of Mataram who were divided into two groups based on their body mass index (BMI). BMI was determined by isolating body weight (kg) by the square of level (m2), and serum MDA levels were resolved utilizing the ELISA technique. The information were investigated utilizing the Mann-Whitney relative test. The results showed that the MDA level in group 2 (obese and overweight) was 1715.27 ng/ml, higher than group 1 (normoweight) with levels of 902.67 ng/ml. However, this difference was not statistically significant, because the p-value was 0.093 (p > 0.05).